Comparative Assessment of Ecological Plasticity of the Steppe Marmot Between Ukrainian and Kazakhstan Populations: Challenges of the Man-Induced Environmental Changes - Ronkin, Vladimir; Tokarsky, Victor; Polchaninova, Nina; Atemasov, Andrey; Koshkina, Alyona; Savchenko, Galina (Frontiers in Ecology and Evolution, 2020)
The steppe marmot inhabits a wide range of open dry grasslands in Eurasia. Throughout this vast area, marmot habitats have undergone major changes due to human activities. Long-term ecological monitoring was conducted in the European steppe marmot settlements (Marmota bobak bobak) in Northeastern Ukraine in 2001–2019. The data obtained were compared with the observations made in M. b. schaganensis settlements in Kazakhstan during the expedition in 2017. The goals of our investigation were (1) to estimate M. bobak ecological plasticity based on general vegetation parameters of its habitats and settlement structure, (2) to relate the population density of the European subspecies to the food base of its habitats, (3) to evaluate the population response of M. b. bobak to the abandonment of cattle grazing, (4) to ascertain new ecological adaptations (if any) to the habitat changes, and (5) to reveal the steppe marmot’s status in the plant–herbivore interaction system in the grasslands of Northeastern Ukraine and Northern Kazakhstan. We have found differences in ecological features of M. b. bobak and M. b. schaganensis. The European subspecies was and continues to be a secondary pasture user. The Kazakhstan subspecies can be both secondary and primary users of the Asian dry steppes. Our studies have shown that the habitats of the European steppe marmot worsened dramatically (due to increased herbage height and cover of uneaten plant species together with litter) in comparison with those of the Kazakhstan subspecies. Presence in diverse habitats with a range of vegetation parameters as well as the differences between the settlement structures of M. b. bobak and M. b. schaganensis demonstrate the high ecological plasticity of the steppe marmot at the species level. At the same time, we have not found any new ecological adaptations that would ensure the survival of M. b. bobak settlements in modern conditions of the total cessation of cattle grazing.